Simplified Canadian Definition for Familial Hypercholesterolemia - Ruel, Isabelle; Brisson, Diane; Aljenedil, Sumayah; Awan, Zuhier; Baass, Alexis; Bélanger, Alexandre; Bergeron, Jean; Bewick, David; Brophy, James M.; Brunham, Liam R.; Couture, Patrick; Dufour, Robert; et al. (Canadian journal of cardiology, 2018)
Familial hypercholesterolemia (FH) is an autosomal codominant lipoprotein disorder characterized by elevated low-density lipoprotein cholesterol (LDL-C) and high risk of premature atherosclerotic cardiovascular disease. Definitions for FH rely on complex algorithms that are on the basis of levels of total or LDL-C, clinical features, family history, and DNA analysis that are often difficult to obtain. We propose a novel simplified definition for FH. Definite FH includes: (1) elevated LDL-C (≥ 8.50 mmol/L); or (2) LDL-C ≥ 5.0 mmol/L (for age 40 years or older; ≥ 4.0 mmol/L if age younger than 18 years; and ≥ 4.5 mmol/L if age is between 18 and 39 years) when associated with at least 1 of: (1) tendon xanthomas; or (2) causal DNA mutation in the LDLR, APOB, or PCSK9 genes in the proband or first-degree relative. Probable FH is defined as subjects with an elevated LDL-C (≥ 5.0 mmol/L) and the presence of premature atherosclerotic cardiovascular disease in the patient or a first-degree relative or an elevated LDL-C in a first-degree relative. LDL-C cut points were determined from a large database comprising > 3.3 million subjects. To compare the proposed definition with currently used algorithms (ie, the Simon Broome Register and Dutch Lipid Clinic Network), we performed concordance analyses in 5987 individuals from Canada. The new FH definition showed very good agreement compared with the Simon Broome Register and Dutch Lipid Clinic Network criteria (κ = 0.969 and 0.966, respectively). In conclusion, the proposed FH definition has diagnostic performance comparable to existing criteria, but adapted to the Canadian population, and will facilitate the diagnosis of FH patients. L’hypercholestérolémie familiale (HF) est une maladie autosomique codominante caractérisée par un taux élevé de cholestérol à lipoprotéines de faible densité (cholestérol LDL) et un risque élevé de maladie cardiovasculaire athéroscléreuse prématurée. Les définitions de l’HF reposent sur des algorithmes complexes basés sur les concentrations de cholestérol total ou de cholestérol LDL, les caractéristiques cliniques, les antécédents familiaux et les analyses de l’ADN souvent difficiles à obtenir. Nous proposons une nouvelle définition simplifiée de l’HF. Pour un diagnostic définitif d'HF, il faut : 1) un taux élevé de cholestérol LDL (≥ 8,50 mmol/l) ou 2) un taux de cholestérol LDL ≥ 5,0 mmol/l (pour les 40 ans et plus); ≥ 4,0 mmol/l (pour les moins de 18 ans); ≥ 4,5 mmol/l (de 18 à 39 ans) lorsque associé à au moins l’une des caractéristiques suivantes : 1) un xanthome tendineux; ou 2) une mutation causale de l’ADN observée dans les gènes LDLR, APOB ou PCSK9 chez le propositus ou les parents de premier degré. L’HF probable concerne les sujets qui ont un taux élevé de cholestérol LDL (≥ 5,0 mmol/l) et qui montrent la présence d’une maladie cardiovasculaire athéroscléreuse prématurée chez le patient ou les parents de premier degré, ou un taux élevé de cholestérol LDL chez les parents de premier degré. Les seuils de cholestérol LDL ont été déterminés à partir d’une importante banque de données qui regroupait > 3,3 millions de sujets. En vue de comparer la définition proposée aux algorithmes actuellement utilisés (c.-à-d. le registre de Simon Broome et le Dutch Lipid Clinic Network), nous avons réalisé les analyses de concordance chez 5987 individus du Canada. La nouvelle définition de l’HF concorde très bien avec les critères du registre Simon Broome et du Dutch Lipid Clinic Network (κ = 0,969 et 0,966, respectivement). En conclusion, la définition proposée de l’HF possède une performance diagnostique comparable aux critères existants, tout en s’adaptant à la population canadienne, et facilitera le diagnostic des patients atteints d’HF.